ANTIMICROBIAL RESISTANCE SURVEILLANCE AMONG INTENSIVE CARE UNITS, ISLAMABAD, PAKISTAN. - Z. Nasir; D.N. Khan; D.N. Noreen (International Journal of Infectious Diseases, 2023)
Intro: Antimicrobial resistance (AMR) is a major factor in patient outcomes in the intensive care unit (ICU). The majority of Intensive Care Unit (ICU) patients are on broad-spectrum antimicrobials, which induces selective antibiotic pressure leading to Antimicrobial Resistance development (AMR) among the microorganisms of ICUs. The aim was to study the occurrence of different types of ICU-acquired infections and the AMR pattern of the bacterial pathogens isolated from them. Methods: It was a descriptive study based on retrospective data collection including culture reports of all patients admitted to the ICUs during the period from April 2022 to June 2022. A total of 3453 isolates were obtained from the clinical specimens of 2,895 patients. Data on sociodemographic characteristics, type of ICU, site of infection, type of HAI, and AMR including co-resistance were collected and analyzed using SPSS version 24. Findings: The ICU infection rate was 62.3%. The most common culture-positive clinical specimen received was tracheal aspirate (35.6%) followed by exudate (22.7%). The most common organisms isolated were Acinetobacter spp from tracheal aspirate and Pseudomonas spp from blood specimens; whereas the predominant organism found in urine, exudate, and sterile fluid specimens were Escherichia coli. Candida species were found in 28.2%. About 17.5% of infections were HAIs, out of which pneumonia (8.43%) was the most common. The antimicrobial susceptibility pattern analysis revealed that most Gram-Negative Bacilli (GNB) were resistant to three or more classes of antibiotics such as cephalosporins, carbapenems, aminoglycosides, tetracyclines, and fluoroquinolones. Multi Drug Resistant (MDR). Conclusion: The rising trend of AMR among hospital-acquired pathogens such as MDR-GNBs, MRSA, and VRE renders an enormous threat to HCWs and other critically ill patients of the ICUs. A robust antimicrobial stewardship program along with educational intervention is critical to combat this issue. Hence, such studies will be a stepping stone in establishing antimicrobial stewardship and regulating antimicrobial use.